Schedule maintenance and repair system of Locomotive - Valiev M.Sh; Kosimov H.R (Proceedings of The ICECRS, 2020)
To increase the efficiency and reliability of locomotives, it is necessary to constantly monitor the operation process. The introduction of modern automatic control and monitoring systems on locomotives is not only a departure from the established state of the equipment, but also an effective and efficient way of processing measurement information that can detect changes in the technical condition of key parts.